A new neodymium–phosphine compound for supercapacitors with long-term cycling stability. Issue 48 (20th May 2021) - Li, Xiaoyu; Chen, Huimin; Yang, Chenyu; Li, Yafeng; Wei, Mingdeng
Abstract : A new neodymium–phosphine compound exhibited an extraordinary capacitance of 951 F g −1 at 0.5 A g −1 with a high capacitance retention of 96% after 10 000 cycles. Abstract : A new neodymium–phosphine compound (Nd–(Ph)3 P) was used for the first time as an electrode for supercapacitors and exhibited an extraordinary capacitance of 951 F g −1 at 0.5 A g −1 with a high capacitance retention of 96% after 10 000 cycles at 10 A g −1, which is the highest capacitance for rare earth based materials in SCs. Such an excellent performance might be due to the fact that this material can provide plenty of electron-active sites for charge storage and electrolyte diffusion can be efficiently promoted.